β-Lactam concentrations monitored in the early phase of community-acquired sepsis in the intensive care unit - Liljedahl Prytz, Karolina; Kryss, Emma; Oxelbark, Joakim; Källman, Jan; Nilsson, Kristofer F; Sundqvist, Martin; Savilampi, Johanna (Journal of antimicrobial chemotherapy, 2025)
Optimal antibiotic treatment is important in the treatment of sepsis. However, patients with sepsis are at risk of suboptimal antibiotic concentrations. This study aimed to evaluate β-lactam antibiotic concentrations during the first 48 h in patients with community-acquired sepsis admitted to the ICU, and to identify variables associated with antibiotic concentrations that were too low or too high. This prospective, observational, single-centre study included patients aged ≥18 years with a high likelihood of infection, a SOFA score of ≥2p, planned β-lactam antibiotic treatment, and ICU admission. The exclusion criteria were ongoing antibiotic treatment and/or nosocomial infections. β-Lactam concentrations were measured up to seven times during the first 48 h. The estimated trough concentrations were divided by the predetermined MIC to generate MIC-multiples for comparison. Patients were allocated to three groups based on the MIC-multiple (MIC× < 1, 1-8 or >8). Fifty patients were included, with a median of seven samples per patient (257 samples). The group with MIC-multiples of <1 (n = 16) was associated with younger age, lower Charlson comorbidity index, Simplified Acute Physiology Score 3, creatinine concentration, and need for noradrenaline. The group with MIC-multiples of >8 (n = 15) had higher creatinine and noradrenaline levels. ICU patients with sepsis are at risk of either too low or too high antibiotic concentrations, and specific patient characteristics may be predictable. Therapeutic drug monitoring in combination with model-informed precision dosing may also help to optimize antibiotic dosing in the early phase of community-acquired sepsis to prevent treatment failure and toxicity.